Numerical relay for overcurrent protection using TMS320F2812 - Goh Y.L. (2023)
Overcurrent protection is a very important element in power systems. This protection is essential in order to minimize disturbances caused by any failure in the system and to ensure continuous power delivery. Overcurrent relays are one of the devices used to achieve these purposes. The overcurrent relays initiate the corrective mechanism to determine the operation time of the relay. Thus, the overcurrent relays must have high reliability and accuracy to detect any fault currents present and determine the operation time. The entire system will be tremendously affected if the relays fail to trip or cause mal-tripping. An overcurrent relay is implemented on a high speed and high performance digital signal processor (DSP). The simulation was carried out using MATLAB/Simulink. Then, the relay was implemented on TMS320F2812 based on two different methods. In the first method, the relay simulation model from MATLAB/Simulink is downloaded into the DSP whereas in the second method, code in C is directly written on the DSP to represent the relay. The relay performance was compared with the IEC 255-3 standard and the outcomes obtained are encouraging.